Deployment modeling for soft cable networks from slack to tension. (1st May 2022) - He, Baiyan; Li, Kangkang; Nie, Rui; Gao, Ben
Highlights: This paper proposed a deployment analysis method for soft cable networks from slack to tension with advantages in convergence, algorithm stability, easy operation, and high efficiency. The proposed method can effectively capture cable networks' time-varying slack/tension state with various topologies, deployment modes, and geometric dimensions. The real-timely updated cable tension and node positions are available for the dynamic coupling with the soft cable network's supporting mechanisms. The mapping relationship between the design parameters and the dynamic behaviors is discussed by analyzing the deployment process of cable networks. Abstract: Cable networks are widely used in space deployable devices and other fields for their large spans, lightweight, and small storage volumes. Among them, the deployable cable network usually turns from a stowed state to a fully deployed configuration and finally forms the working shape. The accurate and effective deployment analysis from slack to tension concerns the stable and efficient service of these cable networks. However, there are still no effective ways to analyze the deployment of cable networks with varying topologies and deployments modes. This paper proposed a general dynamic method for the deployment analysis of cable networks. The cable network is divided into a set of particles, and the deployment process is regarded as a series of time steps. Each node's equations about the force and displacement are formulated and assembled by applying a topological matrix to form the dynamic system model. The cable node's coordinates in the stowed state are calculated and further used to solve the coordinates and tension in the following time step by central difference method. Repeat this process until obtaining all the nodes' positions and cable forces during the deployment. The cables' slack/tension states are evaluated real-timely, and cable tension and node coordinates are updated accordingly, which makes the dynamic coupling with supporting mechanisms possible. The presented method applies to the deployment dynamic modeling and analysis of cable networks with various topologies, deployment modes, and geometric dimensions, with effective, easy operation, good convergence, and high-efficiency features. Graphical abstract: Image, graphical abstract